Smart Tourism: Implementation and Challenges of IoT Technology in Popular Tourist Destinations - Pratama, Tito (Yayasan Pendidikan Belajar Berdikari, 2024)
The purpose of this study is to examine the impact of the application of Internet of Things (IoT) technology on many aspects of the tourism industry, including ease of access, comfort while traveling, security and safety, and overall tourist satisfaction. The findings of the analysis reveal that implementing IoT technology has a significant impact on all dependent variables studied. In particular, the influence on ease of access (total effect coefficient = 0.924, P-value = 0.000) demonstrates a strong and significant association. Significant effects were found for travel convenience (total effect coefficient = 0.770, P-value = 0.000), security and safety (total effect coefficient = 0.590, P-value = 0.000), and overall satisfaction (total effect coefficient = 0.687, P-value = 0.000). The proposed model fit the data well, as evidenced by measures such as SRMR (0.076), d_ULS (0.086), and NFI (0.928). The R-square values for ease of access (0.854), convenience of travel (0.593), security and safety (0.348), and overall satisfaction (0.472) show that the model can explain the majority of the variation in these dependent variables.Overall, the study's findings underscore the relevance of implementing IoT technology to improve the tourist experience at tourist attractions. IoT technologies not only enable access and boost convenience, but they also improve security, safety, and overall tourist pleasure.